En kvalitativ intervjustudie av hur ungdomar i Piteå konsumerar nyhetsmedier - Ek, Jennifer; Larsson-Schulz, Susanna (2012)
We studied how a group of youths in Piteå use news media, what media they use and why they use them. We did a qualitative study with interviews to be able to answer the questions. We did interviews with six students from the gymnasium and then we put the empirics that we got in relation to the Uses and gratification theory and also in relation to earlier research that has been done in this area. The most important thing we got from our study is that the youths uses news media, and mostly the classic medias like newspapers, even though some researchers say that the consumption of classic news medias among youth are low. The classic media that have the largest representation in our study are Piteå-Tidingen because that is the local newspaper in the city. In contrast to the quantitative studies that do exist does the classic news media have a large representation in our research. The choice of media depend mostly on that the youths want local news the give them information about what is happening in the society because they want to be updated about things that concern them. Another important part in the choice of news media depend on what supply they have. In this case which medias the parents use because the youths does still live at home. Validerat; 20120630 (anonymous)